Peran Komunikasi Strategis Penjualan Produk Ecoprint Melalui Media Sosial Facebook Terhadap Minat Beli Konsumen Di Indonesia - Tri Nugraha (IAIN Padangsidimpuan, 2025)
The role of social media, particularly Facebook, is crucial in supporting the sustainability and competitiveness of ecoprint SMEs in the era of digital transformation. Ecoprint, a natural fabric dyeing technique, carries both artistic and eco-friendly values that require effective communication to reach wider markets. This study aims to analyze marketing communication strategies for ecoprint products through Facebook, focusing on the effectiveness of visual and narrative content, online community engagement, and the use of paid promotion features. The research employed a descriptive qualitative approach through content analysis of 50 Facebook posts, in-depth interviews with SME owners and consumers, participatory observation, and an online survey to measure consumer perceptions. The findings reveal that consistent digital communication strategies grounded in sustainability values significantly enhance brand awareness, increase audience engagement by up to 68%, and boost average revenue by 27% within six months. Content emphasizing storytelling about eco-friendly processes and unique patterns proved more effective than conventional promotions in fostering consumer loyalty, with repeat purchases increasing by 35%. Beyond being a promotional tool, Facebook also serves as a consumer preference analytics platform, enabling real-time strategy adjustments and reducing promotional costs by up to 40%. However, limited digital literacy among SME owners remains a primary obstacle to platform optimization. This study contributes theoretically by integrating perspectives of strategic communication, value-based marketing, and digital transformation, while providing practical guidelines for SMEs to manage sustainable marketing communications via social media.Keywords: Strategic Communication; Ecoprint; Facebook Social Media; SMEs; Digital Marketing.